El status de diputado del Parlamento Europeo (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2014)
The MEP status is based in the immunity and the representative mandate. The legal framework. Shows a complex enviroment of powers and rights. However it invites us to theme about an inproved conexion between votes and elected.
Keywords: European Parliament; MEP Statute; Code of conduct; challenges